Following the Thread – Analysis of Fluctuations in the Textile and Apparel Industry - Julia Włodarczyk; Paula Małczęć; Kinga Pala (Annales Universitatis Mariae Curie-Skłodowska Sectio H, Oeconomia, 2021)
Theoretical background: The Polish textile and apparel market is one of the biggest and the most dynamically growing markets in Central and Eastern Europe. This industry is characterized by high dynamics of changes, both seasonal and at the business cycle frequency.